Biodegradability of Fruit and Vegetable Waste (FVW) - Seswoya, Roslinda; Ang, Siew Fen; Shaharoshaha, A’isyah Mardhiyyah (Penerbit UTHM, 2020)
This chapter reviews one of organic fraction of municipal solid waste, which is food waste. It covers the food waste generation rate, environmental issues in managing food waste and food waste disposal /treatment method. The review on the fruit and vegetable waste (FVW) is included in the term of the characterization. This chapter also includes the FVW stabilization method and the FVW digestibility. The methane yield observed from the batch biomethane potential tests (BMP) and the modelling analysis using Modified Gompertz to examine kinetic parameters of biodigestibility of FVW are presented. In addition, FVW is having organic matter as indicated by higher TS/VS ratio, make it is a preferable substrate (sole substrate) for anaerobic digestion.